Navigating Contemporary Ethical Challenges: Murtadha Muthahhari’s Philosophical Insights for Modern Muslims - Putra, Gilang Virmanedi; Rahmaditha, Khairani (Islamic Thought Review, 2024)
This article explores the ethical framework proposed by Murtadha Muthahhari in addressing the moral dilemmas encountered by contemporary Muslims. Motivated by the multifaceted crisis affecting modern Muslim societies, this research seeks to apply Muthahhari’s philosophical insights to contemporary ethical issues. Central to this investigation is Muthahhari’s conceptualization of Ma'rifah Allah (Knowledge of God) and Worship as foundational elements in his ethical philosophy. The study utilizes primary sources, including Muthahhari’s seminal works such as Philosophy of Morals, Perfect Man, and Islamic Moral Philosophy, alongside secondary sources encompassing related scholarly literature. Employing a methodological approach that integrates literature review, inductive reasoning, critical analysis, and heuristic methods, the research elucidates how Muthahhari’s emphasis on aligning human actions with divine commands can lead to a transformative ethical paradigm. The findings suggest that Muthahhari’s philosophy provides a robust framework for resolving the ethical challenges faced by contemporary Muslims, underscoring the transformative potential of grounding ethical conduct in the pursuit of divine pleasure.